‘교양소설’로서 『광장』 읽기 - 이평전(Lee, Pyeong Jeon) (교양교육연구, 2013)
이 논문은 최인훈의 『광장』에 나타난 교양이념과 그것의 재현 방식을 교양소설의 구현이라는 관점에서 살피고 있다. 실제 『광장』에 교양소설이라는 이름을 부여할 수 있는가는 여전히 논쟁적이다. 그럼에도 근대의 역동성이 부여한 성장의 과제에 대한 고투와 기획을 보여주는 이 소설이 교양소설적 면모를 갖추었음은 분명해 보인다. 교양소설은 인간의 완성을 믿는 전통에서 출발해 인간 개개인의 존재를 인정하고 ‘개인’이 주체가 되는 사회, 문화적 조건의 바탕위에서 성립한 소설 장르로 『광장』은 ‘이명준’으로 상징되는 1960년대적 교양 주체를 적극적으로 재현하고 있다. 『광장』은 교양소설의 근본 주제인 자기결정을 통한 개인성의 구현이라는 근대적 과제를 수행하고, 그렇게 구현된 개인이 전체의 일부로서 사회적 통합을 달성해가는 과정, 또는 그것에 실패해 좌절하는 모습이 잘 드러난다. 『광장』에 나타나 ‘개인’과 ‘이데올로기’, ‘공동체 ’ 사이의 긴밀한 관계는 근대 주체의 교양의 성취과정에 다름 아니다. 그러므로 교양소설로서 『광장』을 읽는 것은 분단 이후 한국의 정치, 역사적 상황 변화에 따라 시대와 의미를 달리하는 현실과 이데올로기에 대한 변화된 인식의 배후를 추적하는 일이다. 『광장』의 교양 소설적 성격은 주어져 있는 모든 현실적 조건들이 완전하게 성숙하고 형성된 총체적 인간이라는 지고의 단계에 이르는 한 인간의 주체 형성 과정을 그리면서도 동시에 시대적 억압에 따른 오류와 혼란으로부터 의식적이며 실천적 주체로 이행해가는 과정을 탐색하는 데 있다. 주요 서사들 즉, 이데올로기, 주체, 개인의 발견, 정치 같은 문제들은 최인훈으로 상징되는 당대 지식인들이 1960년대 시공간과 대면하는 교양의 의미 생산 방식과 자기 이해의 담론이 소설을 포함한 사회의 의미화 영역에 자리 잡는 과정을 보여준다. In this paper, we discussed educational philosophy and its reproduction that appeared in the novel of “The square” by Choi, Inhoon in the light of the characteristics of Bildungsroman. Even if the narration of all young man in this novel is no proclamatory statement, the “The square” by Choi, Inhoon clearly shows up a Bildungsroman manner. Of course, it is true there are different perspectives of love, travel and growth of subject for narration, ‘Lee, Myungjun’ who is the protagonist in this novel which was drawn into the close relationship between communities, ideology, and individuals in 1960s is clearly cultured person when so called the ‘Bildung’ was defined as individuals form and expand the subject themselves and the formation of a culture by discovering their place in the society. One of the characteristics of Bildungsroman in “The square” tell the process of growth as a holistic human who is well formed, and fully matured. The other is that the protagonist Lee, Myungjun was drawn to the process of transition to conscious and practical subject from confusion and error caused the suppression of the times. This means that the culture, based on traditional humanism of the bourgeoisie to enrich the power of human, the Korean War, and 4.19 show the growth and practice both individual and society to us at the same time. Both the cultural philosophy of German which is to achieve the completion of t he nation through the subjects who are practicing themselves, and Matthew Anold who is forming the nation dominated bourgeois culture by approving the formation of hegemony for the middle class show the ideological character of all. In this regard, to read “The square” as Bildungsroman has been tracking the recognition of the change for the ideology and KCI Citation Count: 5